Disfungsi Agensi Politik Ulama di Aceh - Muhammad Chabibi (Institut Pesantren KH Abdul Chalim Mojokerto, 2016)
This article discusses how the Ulama in Aceh or it’s so-called with Teungku Dayah affiliated with the Consultative Council of Ulama (Majelis Permusyawaratan Ulama) have experienced the dysfunction of his political agency. Using the Giddens’ theory of structuration , this article yields some conclusions that genealogically and historically the relations between people of Acehnese and Ulama is structural patterns of action pertaining to social, economic, educational and political life. Ultimately, the Ulama action is interpreted as a sacred-religious agency and penetrates into the profane-worldly agency. Aceh's political Ulama have now branched out according to the personal and group human interests.